Segregation of Agronomic Characters in the F2 Generation on Long Beans (Vigna sinensis L.) from Crossing Varieties of Fagiola vs Aura Hijau - Solichah, Urip Jamiati; Anwar, Syaiful; Kusmiyati, Florentina (Universitas Muhammadiyah Malang, 2020)
Crossing is one of the breeding programs that can be done to get better plant varieties. Breeders select to determine the seeds that can be planted on subsequent planting. To increase the success of selection, segregation needs to be determined. The study's main focus was determining the frequency distribution and crop segregation. This research was conducted from November 2018 - January 2019 in Agroecotechnopark and Laboratory of Plant Physiology and Breeding, Diponegoro University, Semarang. This study used F2 seeds from crossing varieties of Fagiola x Aura Hijau. The experimental design was carried out using a single plant design. The results were analyzed using the distribution suitability test and chi-square test. Characters that have a normal distribution are plant height, number of leaves, length of pods, and sweetness. The character that is not normally distributed is pod weight. Two genes are dominant-recessive epistasis controlling pod weight.